2017
DOI: 10.1016/j.molimm.2017.01.023
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and functions of NLRP3 inflammasome during influenza virus infection

Abstract: The NLRP3 inflammasome constitutes a major antiviral host defense mechanism during influenza virus infection. Inflammasome assembly in virus-infected cells facilitates autocatalytic processing of pro-caspase-1 and subsequent cleavage and secretion of proinflammatory cytokines IL-1β and IL-18. The NLRP3 inflammasome is critical for induction of both innate and adaptive immune responses during influenza virus infection. Inflammasome-dependent antiviral responses also regulate immunopathology and tissue repair in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
57
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 79 publications
(188 reference statements)
2
57
0
Order By: Relevance
“…To characterize the bat NLRP3 in response to virus infection, LPS-primed iMACs were infected with H1N1 influenza A virus (IAV), strain A/NWS/33. It is a negative-sense single-stranded RNA (−ssRNA) virus, known to activate the NLRP3 inflammasome 27 . All bat NLRP3 isoforms were significantly less responsive to IAV infection, while viral titres from supernatants were not affected ( Fig.…”
Section: Nlrp3-mediated Inflammation Is Dampened In Bat Immune Cells mentioning
confidence: 99%
See 1 more Smart Citation
“…To characterize the bat NLRP3 in response to virus infection, LPS-primed iMACs were infected with H1N1 influenza A virus (IAV), strain A/NWS/33. It is a negative-sense single-stranded RNA (−ssRNA) virus, known to activate the NLRP3 inflammasome 27 . All bat NLRP3 isoforms were significantly less responsive to IAV infection, while viral titres from supernatants were not affected ( Fig.…”
Section: Nlrp3-mediated Inflammation Is Dampened In Bat Immune Cells mentioning
confidence: 99%
“…NLR family pyrin domain containing 3 (NLRP3) is an important sensor that recognizes both cellular stresses (such as extracellular adenosine triphosphate (ATP), mitochondrial damage and oxidized DNA) [24][25][26] and viral or bacterial infections 27,28 . NLRP3-mediated inflammation has been causally linked to aging and multiple agerelated chronic diseases 29,30 .…”
mentioning
confidence: 99%
“…inflammasome activation [79,82]. It was shown that the M2del29-31 mutant of the influenza virus (lacking amino acids 29-31 from the transmembrane region of the M2 protein) completely failed to stimulate inflammasome activation and release of IL-1β or IL-18 from BMM and BMDCs [79].…”
Section: By Altering Ionic Concentrations Of Intracellular Compartmenmentioning
confidence: 99%
“…Also, a recent study using NLRP3 inhibitor reported that NLRP3 plays a protective role in the early stage of influenza infection, but a detrimental role in the late stage through increased cytokine production and lung cellular infiltrates (39). The NLRP3 inflammasome can be activated by many conditions including a variety of pathogen-and damage-associated molecular patterns and different stresses (45)(46)(47). Therefore, a difference in viral dose, virus production, course of infection, animal facility, and the sex of mice could lead to different results.…”
Section: Aim2 Deficiency Provides Protection Against Iav-induced Lungmentioning
confidence: 99%